Studies on certain haematological and biochemical constituents in cows with retained fetal membranes - RAY, S K H; DASH, H D; MOHANTY, D N; DAS, S; BISOI, P C; BARIK, A K (The Indian Journal of Animal Reproduction, 2023)
Ten cows with retention of foetal membrane (RFM) and six cows delivering normally were included in the present investigation. Blood samples were subjected for estimation of certain haematological and biochemical constituents. The total leucocytic count as well as eosinophil, basophil and monocyte percentage did not vary significantly between cows with RFM and normal cows. Neutrophil count in RFM cases was significantly lower (P < 0.01 ), whereas lymphocyte percent in RFM was significantly higher (P < 0.0 I) than the values for normally delivered cows. The serum calcium, inorganic phosphorous, ALT_ and AST concentration in RFM cases did not differ significantly with normal parturient animals. On the contrary, the ALP activities were significantly higher (P < 0.01) in cows with retained fetal membrane (35.38± 1.69 IU/L) in comparison to normal cows (25.73±1.79 IU/L).